Pengaruh Harga dan Kualitas Layanan terhadap Kepuasan Pelanggan NA Coffee - Rezki, Rendi; Efi, Agusti; Putri, Yuzia Eka (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the effect of price and service quality on customer satisfaction at NA Coffee. The method used is quantitative descriptive research with a causal associative approach. The population in this study were customers who visited NA Coffee during the study period, with a sample of 100 people selected using incidental sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability. The analysis tests used were normality test, multicollinearity test, multiple regression, and ANOVA test (F test) to see the relationship between price variables, service quality, and customer satisfaction. The results showed that price and service quality had a significant effect on customer satisfaction. Prices that are considered reasonable and in accordance with product quality and friendly and responsive service make a major contribution to increasing customer satisfaction. The combination of competitive prices and quality service is very important to achieve optimal customer satisfaction. Therefore, it is recommended that NA Coffee maintain a balance between reasonable prices and good service quality to strengthen customer loyalty and improve its competitive position in the market. NA Coffee also needs to evaluate and improve prices and services periodically to remain relevant to customer needs. Keywords: price, service quality, customer satisfaction